Densification of CaAl2O4 and CaAl4O7 - Singh V.K. (My University, 2025)
Isothermal sintering of calcium monoaluminate and dialuminate powders (−45 μm) has been carried out to study their densification behaviour in the temperature range 1380° to 1450°C. The soaking periods varied from 10 to 240 min. The data were analyzed using Arrhenius equation and the equation D = K log t + C where D is the bulk density and t is the sintering time, K and C are constants. It was found that CaAl2O4 requires an activation energy of 120 KJ.mol−1 and that CaAl4O7 requires 165 kJ.mol−1. © 2000 Taylor and Francis Group, LLC.